Co-Creation for Social Innovation in the Ecosystem Context: The Role of Higher Educational Institutions - Kumari, Richa; Kwon, Ki-Seok; Lee, Byeong-Hee; Choi, Kiseok (Sustainability, 2020)
This study examined the role of Higher Educational Institutions (HEIs) in promoting, creating, and sustaining social innovation. Recently, HEIs have extended their contribution beyond the traditional function of teaching and research to perform in socio-economic problem-solving. Considering the increasing trends of higher education involvement in social innovation practices, this study tries to examine the tools such as learning processes and systemic thinking approach that could be helpful to align the function and responsibilities of HEIs towards social innovation. The objective is to develop a theoretical understanding of the "co-creation for social innovation" concept and to understand the functions and activities of HEIs that can contribute to this process. To promote co-creation for social innovation, HEIs should actively encourage collaborative learning tools that focus on open platforms for collective action and systemic change that help them to engage with society and strengthen their collaboration with social actors. Different activities such as mutual learning and knowledge diffusion using a transdisciplinary approach, technology-based learning and collaboration, and relational transformation are key enablers that can promote social innovation.
Place: Basel Publisher: Mdpi WOS:000521955600307 Organsimes de soutien pour bien comprendre le rôle des établissements d’enseignement supérieur Adhésion et pérennisation, puisqu’il est abondamment question de changements systémiques 2e section article (p. 13) : mise en évidence de l’apparition de nouveaux concepts et espaces collaboratifs dans les univeristés. Approches collaboratives : la Table 3 est particulièrement intéressante. Les établissements d’enseignement supérieurs peuvent aussi contribuer à l'innovation sociale. Toutefois, elle doit sortir de l’institutionnel et s’ouvrir dans les modes de formations des étudiantes et étudiants. L’intégration des capacités (et changements de comportenments) liés à l’innovation sociale gagne à être intégré dans la formation.
Keywords: Changement systémique; Co-création; Compétences; Formation; Laboratoires d'innovation; Libre accès; Rôle des universités

Co-Creation for Social Innovation in the Ecosystem Context: The Role of Higher Educational Institutions - Kumari, Richa; Kwon, Ki-Seok; Lee, Byeong-Hee; Choi, Kiseok (Sustainability, 2020)
This study examined the role of Higher Educational Institutions (HEIs) in promoting, creating, and sustaining social innovation. Recently, HEIs have extended their contribution beyond the traditional function of teaching and research to perform in socio-economic problem-solving. Considering the increasing trends of higher education involvement in social innovation practices, this study tries to examine the tools such as learning processes and systemic thinking approach that could be helpful to align the function and responsibilities of HEIs towards social innovation. The objective is to develop a theoretical understanding of the "co-creation for social innovation" concept and to understand the functions and activities of HEIs that can contribute to this process. To promote co-creation for social innovation, HEIs should actively encourage collaborative learning tools that focus on open platforms for collective action and systemic change that help them to engage with society and strengthen their collaboration with social actors. Different activities such as mutual learning and knowledge diffusion using a transdisciplinary approach, technology-based learning and collaboration, and relational transformation are key enablers that can promote social innovation.
Number: 1 Place: Basel Publisher: Mdpi WOS:000521955600307
Keywords: Co-création; Libre accès; Rôle des universités